2023
DOI: 10.3390/met13111897
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparative Investigation of Duplex and Super Duplex Stainless Steels Processed through Laser Powder Bed Fusion

Leonidas Gargalis,
Leonidas Karavias,
Joachim S. Graff
et al.

Abstract: The aim of this paper was to compare duplex (DSS) and super duplex stainless steel processed by laser powder bed fusion (LPBF) based on the process parameters and microstructure–nanomechanical property relationships. Each alloy was investigated with respect to its feedstock powder characteristics. Optimum process parameters including scanning speed, laser power, beam diameter, laser energy density, and layer thickness were defined for each alloy, and near-fully dense parts (>99.9%) were produced. Microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Microcrystalline grain boundary austenite (GBA) was observed at the grain boundaries, exhibiting an allotriomorphic shape and morphology ( Figure 4 b). LPBF-related studies [ 5 , 6 , 7 , 8 , 9 , 11 , 12 , 14 , 21 , 28 , 29 ] have reported that extremely high cooling rates inhibit the formation of sigma phase in as-printed conditions. Additionally, an excess of nitrogen saturation within the ferrite matrix has been found to induce the formation of chromium nitride precipitates due to the formation of Cr-rich regions at grain boundaries (GB).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microcrystalline grain boundary austenite (GBA) was observed at the grain boundaries, exhibiting an allotriomorphic shape and morphology ( Figure 4 b). LPBF-related studies [ 5 , 6 , 7 , 8 , 9 , 11 , 12 , 14 , 21 , 28 , 29 ] have reported that extremely high cooling rates inhibit the formation of sigma phase in as-printed conditions. Additionally, an excess of nitrogen saturation within the ferrite matrix has been found to induce the formation of chromium nitride precipitates due to the formation of Cr-rich regions at grain boundaries (GB).…”
Section: Resultsmentioning
confidence: 99%
“…The microstructures consist mostly of ferrite with small amounts of austenite found mainly at grain boundaries and within the ferritic matrix, as well as limited intragranular austenite. LPBF presents challenges in achieving a well-balanced duplex microstructure due to its rapid cooling rate, often resulting in a predominantly ferritic microstructure in the as-printed condition [ 5 , 8 , 21 ]. To overcome this limitation, post-processing annealing is necessary [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited literature on PBF-LB-processed DSS alloys [12][13][14][15][16][17][18][19][20] is primarily focused on documenting the effects of processing parameters on the porosity, with relatively less attention devoted to microstructural analysis and understanding of microstructure-mechanical behavior relationships. For example, Davidson and Singamneni [14,15] conducted two investigations to examine the impact of processing conditions on the build quality of DSS, specifically focusing on porosity and certain microstructural features.…”
Section: Introductionmentioning
confidence: 99%
“…In the original publication [1], there was a mistake in Table 6 as published. We erroneously reported the values included in Table 6, which should be deleted.…”
mentioning
confidence: 99%